The Stress in the Working Environment: A General Point of View of the Effects of Stress on the Productivity of Nurses - Sadiku(Alterziu), Violeta (European Journal of Multidisciplinary Studies, 2016)
The main focus of this study is the qualitative analysis of the phenomenon of stress and its influence on the productivity in the working environment. In order to create a clear point of view in the stress-productivity ratio, this study has been channeled in the profession of nurses. For this reason there were selected 8 nurses from the General Hospital in the city of Elbasan, from which 7 are females and 1 is a male. Every member underwent a structured interview, which contains 15 claims. From the analysis of the results it was concluded that the stress has a wide range of spreading and a considerable amount of influence among nurses and their productivity. Furthermore, there were identified some factors and sources of stress such as: the condition of the patients, the lack of working tools and medicaments, people’s irresponsibility, the lack of respect toward the hospital’s rules, misunderstandings, the work overload and the relationship with the colleagues. Towards the end of the study there are offered some recommendations for the stress management in the working environment, based on the elements which were evidenced from the data analysis
Keywords: Stress, Productivity, service quality, working environment.